Efektivitas Model Pembelajaran Tutor Sebaya Dalam Meningkatkan Kemampuan Membaca Al-Qur'an Santri Pada Program Pengajian Ba'da Subuh Di Pondok Pesantren Tebuireng - Dewi Zainul Alfi; Khoirotul Idawati (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2022)
Peer tutor learning model is a way to learn friends with friends. The focus in this study is how the peer tutoring learning model, how effective is the use of peer tutoring learning model in improving the ability to read the Qur’an of students in early dawn recitation program, what are the supporting factors and obstacles. This study used a qualitative descriptive approach with a phenomenology approach. Data obtained through observation, interview, and documentation. This study resulted in the findings peer tutor learning model at Tebuireng Islamic Boarding School 2, namely every senior students or student who are generally older teach their juniors. The selection of tutors on the recommendation of ustadz/ustadzah with various criteria. The use of peer tutoring learling model can be said to be effective because the learning objectives and targets are minimally achieved. The supporting factors of the use of the learning model are the strong desire to teach in the students, the lack of qualified teachers and students. While the inhibiting factors for using this learning model are students who are not serious in learning and tutors are still confused in dealing with sleepy students.